Investigating Overreaction and Underreaction in Initial Public Offerings - Enow, Samuel Tabot (International Journal of Economics and Financial Issues, 2024)
Investors often overreact and underreact to new information in stock markets which has an exaggerated effect on the stock price. This has led to possible mispricing of Initial public offering. The aim of this study was to investigate overreaction and underreaction for selected stocks in the Frankfurt stock exchange. This study employed a Threshold GARCH model on a sample of eight initial public offerings from 2017. The findings of this study revealed the presence of overreaction and underreaction in the selected stocks where the leverage coefficients were found to be statistically significant in some cases. These findings provide valuable insights as the high risk of investing in initial public offerings may not be compensated for the level of return. Also, investors can minimise the risk of investing in initial public offerings by adding a risk coefficient to their pricing.